Entrepreneurial intention among students of public accounting and business administratio at the Universidad Francisco de Paula Santander in San José de Cúcuta - Luis Alexander Rojas Sánchez; Esther Adriana Maldonado Jauregui; Ana Milena García Mogollón (Conocimiento global, 2026)
Entrepreneurship constitutes a relevant alternative for economic and social development in regional contexts where formal employment opportunities are limited. In this context, the present research aimed to analyze the level of entrepreneurial intention among students of the Business Administration and Public Accounting programs at the Universidad Francisco de Paula Santander, Cúcuta, with the purpose of identifying the perceptions, attitudes, and factors associated with interest in creating business initiatives. The study was developed under a quantitative approach, with a descriptive cross-sectional design. The sample consisted of 227 students enrolled in the aforementioned programs. For data collection, the Entrepreneurial Intention Questionnaire (EIQ) was applied, an instrument that measures variables related to attitude toward entrepreneurship, perception of social support, and entrepreneurial self-efficacy. The results showed that a significant proportion of students present favorable levels of entrepreneurial intention, expressing willingness to develop business projects in the future. Likewise, it was identified that factors such as confidence in one's own abilities, perception of opportunities in the environment, and support from the academic context positively influence the intention to undertake entrepreneurial activities. In conclusion, the findings show that the university environment constitutes a favorable setting for the strengthening of entrepreneurial competencies, which highlights the importance of promoting institutional strategies aimed at fostering innovation, company creation, and entrepreneurial education among students.